Corpus-informed research and learning in ESP : issues and applications - Boulton, Alex; Carter-Thomas, Shirley; Rowley-Jolivet, Elizabeth (Studies in corpus linguistics, 2012)
These specially-commissioned studies cover corpus-informed approaches to researching, teaching and learning English for Specific Purposes (ESP). The corpora used range from very large published corpora to small tailor-made collections of written and spoken text, as well as parallel and contrastive corpora, in both the hard and softer sciences. Designed to tackle the problems faced by a variety of first- and second-language ESP users (specialised translators, undergraduates, junior and experienced researchers, and language trainers), the breadth of approaches enables treatment of issues central.